PARADIGMA KERUSAKAN LINGKUNGAN DALAM TINJAUAN AL-QUR’AN - Nizaruddin, Akhmad (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
The Qur'an pays attention to the environment. and give a strong warning to humans if they cause damage. The focus of the article is how the Al-Qur'an interprets verses related to environmental destruction; and what are the terms regarding environmental destruction in the Koran. The current research focus is literature. The main source of this research is the Koran. Secondary sources are the tafsir books of the ulama. In conclusion, the terms used in the Qur'an related to environmental damage are fas?d and halaka. The term fas?d has several meanings including; deviant and useless behavior, disorder/disorder, destructive behavior, neglect or not caring, environmental damage. The term halaka also has several meanings, including: loss of something from oneself, wasting one's possessions, loss or disadvantage, destruction in the form of natural damage, death or passing away, fan?' or the opposite of baq?', destruction and collective destruction. The Qur'anic terms used as causes of environmental damage include: tabzir, israf, itraf.